2D elastic full‐waveform imaging of the near‐surface: application to synthetic and physical modelling data sets. Issue 3 (1st December 2012) - Bretaudeau, François; Brossier, Romain; Leparoux, Donatienne; Abraham, Odile; Virieux, Jean
Abstract : Standard seismic methods are generally not well adapted to provide sharp quantitative images of the first few metres of underground. A two‐dimensional full‐waveform inversion of land seismic data, based on frequency‐domain viscoelastic modelling, offers a promising approach to take advantage of the full complexity of seismograms and to simultaneously build 2D images of V P and V S parameters. In order to understand the behaviour of this method in a near‐surface context and anticipate the corresponding field applications, we perform this investigation by applying waveform inversion on a simple layered medium. We first use synthetic data obtained from numerical modelling and then we employ laboratory data obtained by small‐scale physical modelling. We demonstrate that such a near‐surface 2D model can be quantitatively determined even in a realistic situation where the data are dominated by high‐amplitude surface waves. A comparison of results derived for the same medium from ideal synthetic data and noisy experimental data allows detecting anomalies in the reconstruction of velocity models due to the experimental nature of the data used.